Ambiente institucional e políticas públicas para o biogás proveniente da suinocultura - Zanella, Makerli Galvan (2012)
This work aims to analyze the institutional environment of the biogas from the concepts of New Institutional Economics (NIE) addressing the set of rules, laws, legislation and other actions that will define the influences of economic agents, public policies aimed at this alternative source of energy, which can generate income and development, and thus provide economic exploitation and promote competitiveness. Besides, the biogas originated by swine manure is presented as an alternative to the Brazilian energy deficit in a global scenario of increasing concern about the impact of the consumption of fossil fuels on the environment. Among the environmental impacts caused by the swine industry that stands out is the contamination of water courses, which may occur directly, through the release of waste into rivers, streams or lakes and, indirectly, through runoff in pastures and crops fertilized with manure, however, when relocated, can generate income and improve the environment with the use of fertilizer and biogas, allowing alternative energy in rural areas and minimizing environmental impact. The viability of the biogas energy recovery depends substantially on the scale of projects, it also appears competitive when compared with fossil fuels used in industry and transport sector. Despite the existing incentive mechanisms to the energy use of biogas, and incentives for alternative sources of renewable energy in Brazil, several regulatory barriers, institutional, economic and technological hinder the effective utilization of this source. Thus, this study indicates the need for greater coordination between the different spheres of government, private sector and research institutions and development to formulate effective policies to promote better energy use of biogas in Brazil. The principal measures to achieve these objectives include free access of energy renewables to the electricity market, measures of fiscal and financial incentives and efforts in research, development and demonstration.